2010
DOI: 10.1007/s12550-010-0051-x
|View full text |Cite
|
Sign up to set email alerts
|

Proteome analysis of Aspergillus ochraceus

Abstract: Genome sequencing for many important fungi has begun during recent years; however, there is still some deficiency in proteome profiling of aspergilli. To obtain a comprehensive overview of proteins and their expression, a proteomic approach based on 2D gel electrophoresis and MALDI-TOF/TOF mass spectrometry was used to investigate A. ochraceus. The cell walls of fungi are exceptionally resistant to destruction, therefore two lysis protocols were tested: (1) lysis via manual grinding using liquid nitrogen, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 46 publications
1
3
0
1
Order By: Relevance
“…While grinding in liquid nitrogen ensured a better cooling of the sample, cell disruption via beads has a very low personal deviation. Extending previous studies [ 23 , 42 , 43 ], we were able to show that the subsequent extraction protocol has a higher impact on the total protein yield than the initial cell disruption. We demonstrated that a higher number of proteins was obtained when solubilisation of the hardly soluble protein fraction was achieved by additional steps.…”
Section: Discussionsupporting
confidence: 79%
See 1 more Smart Citation
“…While grinding in liquid nitrogen ensured a better cooling of the sample, cell disruption via beads has a very low personal deviation. Extending previous studies [ 23 , 42 , 43 ], we were able to show that the subsequent extraction protocol has a higher impact on the total protein yield than the initial cell disruption. We demonstrated that a higher number of proteins was obtained when solubilisation of the hardly soluble protein fraction was achieved by additional steps.…”
Section: Discussionsupporting
confidence: 79%
“…Nearly all new studies needed an adaptation of the protein extraction methodology. In general, fungi are known to have rigid and complex cell walls, which is why a special focus on cell wall disruption is required during sample preparation [ 17 , 22 , 23 ].…”
Section: Introductionmentioning
confidence: 99%
“…A 5600+ TripleTOF (Sciex, USA) was used for identification (Information dependent acquisition, IDA) and quantification (sequential window acquisition of all theoretical fragment‐ion spectra, SWATH) runs. For the IDA experiments, a 140 ms survey scan (TOF‐MS) was performed, from which the top 20 ions were selected for MS/MS analysis, each a 100 ms scan .…”
Section: Comparison Of the Three Different Databases Usedmentioning
confidence: 99%
“…Several approaches are described and optimized by different researchers; however there are still no general protocols available to extract proteins from any given sample [27]. The combination of TCA and acetone is reported as effective and easy for precipitation of fungal proteins [28,29]. Other strategies like 100 mM ammonium acetate in methanol were described also for fungal tissues [21].…”
Section: Protein Enrichmentmentioning
confidence: 99%